Comparative Study of Carbamazepine and Gabapentin in the Treatment of Trigeminal Neuralgia - Dr. Amruta Vithalkumar Rajmanya; Dr. Rajesh Dineshkumar Dabi; Dr. Tejendra Sukdeo Chaudhari; Dr. Chetan Ramesh Chaudhari (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
facial pain. Carbamazepine is traditionally the drug of choice; however, gabapentin has been proposed as an alternative due to its favorable safety profile. This study aims to compare the efficacy and safety of carbamazepine and gabapentin in the management of trigeminal neuralgia. Methods: In this randomized, controlled trial, 80 patients diagnosed with trigeminal neuralgia were allocated into two groups to receive either carbamazepine or gabapentin. The primary outcome measured was the reduction in pain intensity, assessed using the Visual Analog Scale (VAS). Secondary outcomes included side effect profiles and patient preference. Data were collected at baseline and monthly intervals over a six-month period. Results: Both carbamazepine and gabapentin groups showed significant pain relief (p>0.05). There was no statistically significant difference in the effectiveness of pain reduction between the two drugs (p=0.42). However, gabapentin was associated with fewer and milder side effects and was preferred by patients over carbamazepine (p=0.04). Conclusion: Carbamazepine and gabapentin are both effective in the treatment of trigeminal neuralgia. Gabapentin, however, may offer an advantage in terms of tolerability and patient satisfaction, making it a compelling alternative to carbamazepine for some patients.